THEMATIC ANALYSIS ON TAKHARRUJ DIVISION IN ISLAMIC INHERITANCE ESTATE DISTRIBUTION - Noratiqah Ramli; Noramyfatin Kamaruzzaman; Noraziah Abd Rashid; Norhaifa Ganti; Mohd Khairy Kamarudin; Norakmal Mardhiah Aimi Mizan (Journal of Islamic, Social, Economics and Development, 2021)
Takharruj division is one of the methods for inheritance estate division amongMuslim heirs. This type of division could facilitate the process of inheritance estatemanagement which is a major problem for Muslims in Malaysia. Therefore, this study aimedto identify the factors that inspire the heirs to succeed inheritance estate via takharruj divisionbased on authority perception and experience. Semi-structured interview was conducted amongofficers at Small Estate Division Unit. Thematic analysis was employed to determine potentialfactors of takharruj for inheritance estate distribution. The result highlight that the foremostreasons of takharruj division being chosen as the inheritance estate division were relationshipamong the heirs and the position of inheritance estate. Relationship among heirs can be definedas siblings’ affection, strengthening relationship’ and needs of other heirs. Whereas positionof inheritance estate referred to land scarcity and multiple ownership. Thus, it was suggestedthat policy makers should formulate specific guidelines related to inheritance estatemanagement which could assist the heirs to manage the estate effortlessly and effectively.